Biofuels from low-temperature microwave and conventional pyrolysis of sewage sludge - Wahi, Rafeah; Idris, Azni; Mohd Salleh, Mohamad Amran; Khalid, Kaida (Institute of Science Universiti Teknologi MARA, 2006)
The use of microwave pyrolysis as an alternative for sewage sludge reutilization was investigated. This paper evaluates the basic chemical characteristic of the bio-fuel obtained in low-temperature microwave pyrolysis in comparison to that of the conventional pyrolysis. In this study, sewage sludge was dried and pyrolyzed in a single process at laboratory scale. Sewage sludge was placed in a quartz reactor, which in turn was placed in a microwave cavity oven. Graphite was used as microwave absorber. The pyrolysis temperature was moderate (at 650 °C) with five minutes heating. Conventional pyrolysis of sewage sludge by using fluidized bed reactor at similar temperature but lower heating rate was conducted for comparative purpose. It is found that microwave pyrolysis of sewage sludge at 650 °C gives rise to formation of 27.7% carbonaceous residue (char), 5.6% pyrolytic oil and 66.7% non-condensable gases (dry basis). On the other hand, 47.3% of char, 14.2% of oil and 39% of non-condensable gases were produced in conventional pyrolysis. Microwave and conventional pyrolysis of sewage sludge at moderate temperature yield pyrolytic oils with calorific values of 28852 and 37194 kJ/kg respectively, which is higher than that of lignite and subbituminous coal (23200 kJ/kg) thereby reflecting the potential of this fraction as fuel material.